Global citizenship and environmental justice - Shallcross, Tony; Robinson, John, 1950- (At the interface/probing the boundaries, 2006)
This book focuses on the concepts of environmental justice and global citizenship from a number of different disciplinary perspectives with the intention of promoting at the very least some interdisciplinary understandings. Initially presented as papers at an interdisciplinary conference on the themes of environmental justice and global citizenship in Copenhagen in February 2002, the chapters in this volume were chosen by election by those attending the conference. They represent the emergent differences of opinion and glimmers of agreement in the conference as discussions of environmental just.